Papel do tabagismo no turnover de colágeno e expressão gengival de TIMP-1 e MMP- 8 na periodontite crônica - Carolina Ferreira Franco (2008)
The aim of this paper was to evaluate the collagen turnover and its correlation to TIMP-1 and MMP-8 expression in gingival tissue of smokers and non-smokers periodontal patients. Gingival samples of 14 non-smokers patients with periodontal disease (PD) 10 periodontal smokers patients (S) and 10 controls (C) were harvested during periodontal surgery and stored frozen at -80oC until manipulation. Gingival collagen was analyzed through picrosirius staining and gingival expression of MMP-8 e TIMP-1 was determined by immunohistochemistry. Gingival tissue from group C and S showed smaller proportion of green fibers (28,54% and 27,98%, respectively) and, greatest proportion of red fibers (71,9% and 72,2%, respectively) than gingival tissue from PD group (46,81% and 53,43%, respectively), indicating a turnover impairment associated to mature type I collagen retention. This findings were statistically significant (p0,01). MMP-8 and TIMP-1 immunostaining was intense in epithelium and connective tissue of samples from all the 3 groups. Only immunostaining of superficial layer of S group was statistically different from that in group PD (p=0,003). There was statistical correlation (0,773; p=0,005) between MMP-8 and TIMP-1 immunostaining in superficial epithelial layer, suggesting balance. There was no statistical correlation between red/ green fibers proportion. These results suggest that the fibrous gingival tissue of smokers with PD is associated with greatest type I mature collagen fibers amounts and smaller collagen turnover. However these changes do not seem to be inflected by TIMP-1 and MMP-8 expression in samples collected after periodontal treatment.